Malnutrition and violent conflict in a heating world: A mediation analysis on the climate–conflict nexus in Nigeria - Belli, Anna; Villa, Victor; Mastrorillo, Marina; Scognamillo, Antonio; Song, Chun; Ignaciuk, Adriana; Pacillo, Grazia (SAGE Publications, 2025)
Climate variability is increasingly gaining recognition as a factor exacerbating risks to peace in Africa, particularly in contexts characterized by weak institutions and fragile agri-food systems. Existing literature has highlighted the intricate indirect pathways that can lead to increasing conflicts following a climatic shock, including reduced agricultural yields, increased food insecurity, and other socio-economic channels that are highly context-specific as well as difficult to quantify. This study investigates the nexus between climate variability (proxied by temperature anomalies) and violent conflicts as mediated by child acute malnutrition in Nigeria. Starting from previous quantitative analyses that implicitly assumed the existence of a singular transmission pathway linking climate variability to conflict, this study employs a structural equation model that accommodates the presence of multiple, albeit unobserved, mediating factors. In doing so, it pioneers the use of children’s nutritional indicators as mediating factors to capture the multidimensional nature of the climate–conflict relationship. The novel approach proposed for this analysis increases the accuracy of estimating the indirect impacts of climate variability on conflict, as mediated by child nutritional outcomes, and contributes to the literature linked to the humanitarian, development and peace nexus. From a policy perspective, our findings aim to inform and support identifying policies and interventions aimed at mitigating the threat posed by climate variability to human security through the nutrition channel.